Conservative Surgery for Right Colon Perforation Leads to Better Long-Term Outcomes in Children: A 21-year Experience - Chau-Jing Chen; Jen-Pin Chuang (Pediatrics and Neonatology)
There is no consensus on standard treatment for right colon perforation in pediatric patients. We reviewed our cases over the past 21 years, comparing the effects of different operations to the long-term growth of patients. Methods: From February 1990 to October 2011, 29 patients of right colon perforation were enrolled in our analysis after excluding tumors, diverticulum, volvulus, and tuberculosis. Clinical information was collected from medical records, and analysis was done over 26 cases younger than 10 years at the time of the treatment. Surgical options included primary repair (D group, 12 cases), segmental resection (S group, 5 cases) and right hemicolectomy (H group, 9 cases). The length of postoperative stay, complications, and body weight growth in body weight percentile curve chart at last follow-up visit in each group were compared by analysis of variance. Results: Of the 26 patients who underwent the right colon perforation treatment, cecum perforation was found in 16 (62%), ascending colon perforation in six (23%), transverse colon perforation in three (12%), and combined ascending and transverse colon in one (4%). No mortality or anastomotic leakage occurred. The mean length of postoperative stay was shorter in the D group than in the S and H groups but without statistical significance (mean 10.9 days vs. 11.6 days and 17.9 days, respectively). Long-term body weight growth was significantly better in the D group (+26.3 ± 22.2 percentile) than the H group (−4.8 ± 8.0 percentile; p = 0.02). Conclusion: For right colon perforation in children, simple closure following debridement has long-term benefits over more extensive resections.